Information Networking. Towards Ubiquitous Networking and Services International Conference, ICOIN 2007, Estoril, Portugal, January 23-25, 2007, Revised Selected Papers - Vazão, Teresa; Freire, Mário M.; Chong, Ilyoung (Computer Communication Networks and Telecommunications, 2008)
This book constitutes the thoroughly refereed post-conference proceedings of the International Conference on Information Networking, ICOIN 2007, held in Estoril, Portugal, in January 2007. The 82 revised full papers included in the volume were carefully selected and improved during two rounds of reviewing and revision from a total of 302 submissions. Topics covered include sensor networks; ad-hoc, mobile and wireless networks; optical networks; peer-to-peer networks and systems; routing; transport protocols; quality of service; network design and capacity planning; resource management; performance monitoring; network management; next generation Internet; and networked applications and services.